Topological engineering of two-dimensional ionic liquid islands for high structural stability and CO2 adsorption selectivity - Wang, Chenlu; Wang, Yanlei; Gan, Zhongdong; Lu, Yumiao; Cheng, Qian; Huo, Feng; He, Hongyan; Zhang, Suojiang (Chemical science (Cambridge), 2021)
Ionic liquids (ILs) as green solvents and catalysts are highly attractive in the field of chemistry and chemical engineering. Their interfacial assembly structure and function are still far less well understood. Herein, we use coupling first-principles and molecular dynamics simulations to resolve the structure, properties, and function of ILs deposited on the graphite surface. Four different subunits driven by hydrogen bonds are identified first, and can assemble into close-packed and sparsely arranged annular 2D IL islands (2DIIs). Meanwhile, we found that the formation energy and HOMO–LUMO gap decrease exponentially as the island size increases via simulating a series of 2DIIs with different topological features. However, once the size is beyond the critical value, both the structural stability and electrical structure converge. Furthermore, the island edges are found to be dominant adsorption sites for CO2 and better than other pure metal surfaces, showing an ultrahigh adsorption selectivity (up to 99.7%) for CO2 compared with CH4, CO, or N2. Such quantitative structure–function relations of 2DIIs are meaningful for engineering ILs to efficiently promote their applications, such as the capture and conversion of CO2.